Disentangling the Evolutionary History of the Woody Species in Earth's Most Diverse Tropical Savanna - Pontara, Vanessa; Dexter, Kyle G.; Rezende, Vanessa Leite; Silva, Valéria Flávia Batista; Campos, Prímula Viana; Bueno, Marcelo Leandro (Journal of biogeography, 2025)
ABSTRACT Aim We investigate the evolutionary structure of vegetation assemblages in the Cerrado Domain, the main extent of savanna in the American Tropics, a biodiversity hotspot, to understand the role of ecological and geographical factors in constraining plant diversification and shaping biogeographic patterns across this complex mosaic of environments. We test the following predictions: (1) savanna assemblages form a distinct evolutionary group, rather than grouping with forest assemblages from adjacent biogeographic regions; (2) moist forests contain the highest phylogenetic diversity, followed by dry forests and savannas and (3) edaphic variables are stronger predictors of evolutionary group differentiation than climatic variables. Location Cerrado, Brazil. Methods Our data set comprises 3072 tree species, belonging to 656 genera and 151 families, found across 1165 assemblages. We used a phylogenetically informed ordination analysis to place assemblages in a multivariate space, followed by K‐means clustering to identify the main evolutionary groups of tree assemblages. To determine which environmental variables were associated with the evolutionary groups found, we implemented classification tree approaches. We quantified both the unique and shared phylogenetic diversity among evolutionary groups and identified the lineages most strongly associated with each evolutionary group using an indicator analysis. Results We find a clear evolutionary differentiation between savanna and forest assemblages, pointing to the importance of fire and water availability in driving turnover in evolutionary lineage composition of tree communities in the Cerrado Domain. When dividing assemblages into three evolutionary groups, the forest group splits into deciduous versus evergreen/semideciduous subgroups. The evergreen and semideciduous forests harbour the highest overall and unique phylogenetic diversity, and deciduous forests the second highest, but the savanna group also contains a significant portion of unique woody angiosperm evolutionary diversity. Conclusions We identified that savannas assemblages constitute a distinct evolutionary group. Tree species that can inhabit fire‐prone areas belong to a restricted set of phylogenetic lineages, giving the savannas in the Cerrado Domain a unique evolutionary identity. Dry forests also constitute a unique evolutionary group. Given the marked evolutionary variation of tree assemblages across the Cerrado Domain, it is imperative to recognise and address the specific conservation challenges faced by each group (savanna, evergreen and semideciduous forest and tropical dry forest) to ensure the preservation of this biodiversity hotspot.